PELATIHAN PRODUKSI UNTUK MENGOPTIMALKAN USAHA KECIL KERIPIK PANGSIT DI DESA LENDANG NANGKA - Bawa Susana, I Gede; Wiryajati, I Ketut; Adhi W.A., I G.A.K. Chatur; Perdana Putra, I Ketut; Alit, Ida Bagus (Universitas Mataram, 2025)
Economic development in the dumpling chips business requires cooperation from the community and related agencies. One of the efforts made by the community service team is training in pangsit chip production. This is necessary because small businesses in Lendang Nangka Village face various challenges in developing their businesses. Production is still carried out traditionally, which has an impact on the lack of uniformity in product quality. One of the main challenges is the limited knowledge and skills needed to produce quality and consistent products. The purpose of Community Service is to strengthen small entrepreneurs in Lendang Nangka Village by improving production skills so that they can make good quality and consistent products. The activity method through training carried out by the Community Service Team and the Cooperatives and SMEs Service, covers aspects of improving technical skills in the production process. Through the production process, training is provided on how to enhance the quality of the product through the use of better techniques and raw materials. The results of community service give an understanding and skills related to pangsit chips raw materials and how to print, fry, dry, and package products. This can be used as a guideline to ensure that the pangsit chips produced are of good quality and can be stored properly. By overcoming existing challenges and utilizing existing opportunities, this program is expected to have a positive impact on regional economic development. Some things related to packaging are new knowledge for pangsit chip artisans. Pangsit chips artisans are interested in using packaging other than plastic to maintain product quality and use packaging for various sizes of their products.